Listy Jerzego Giedroycia do György’a (George’a) Gömöriego (1958–1968) - Lagzi, Gábor (Archiwum Emigracji. Studia – Szkice – Dokumenty, 2017)
JERZY GIEDROYC’S LETTERS TO GYÖRGY (GEORGE) GÖMÖRI (1958–1968) The most important contributor discussing Hungarian affairs in the Parisian Kultura was a 1956 immigrant György (George) Gömöri, a Polish studies specialist living in England, a literary scholar, poet and translator. Thanks to Gömöri Hungarian affairs were discussed for decades in Kultura (and, to a lesser degree, in the periodical Zeszyty Historyczne). An important background for the Hungarian affairs discussed in the publications of the Instytut Literacki is provided by the correspondence between György Gömöri and Jerzy Giedroyc, who exchanged letters, at varying frequency, from 1958 to 2000 (most letters were written in the 1950s and 1960s). The cooperation of Jerzy Giedroyc and György Gömöri has proved beneficial to both of them. Giedroyc had at his disposal an expert, correspondent and specialist in Hungarian matters willing to contribute to Kultura and Zeszyty Historyczne, while the Hungarian specialist in Polish studies and literature gained a platform to voice his thoughts in one of the most important periodicals of the Polish émigré community where he could present “the Hungarian perspective,” which made him relatively well-known among the Poles living in exile.